THE EFFECTIVENESS OF EXEMPLARY AND HABITUAL METHODS IN SHAPING STUDENTS' MORALS AT SMA NEGERI 1 BENGKUNAT - Anggara, Waliyan; Tadjuddin, Nilawati (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2025)
This study explores the effectiveness of exemplary and habituation methods in learning morals at SMA Negeri 1 Bengkunat, Ngaras District, Pesisir Barat Regency. This research uses a qualitative approach with a descriptive method, focusing on understanding phenomena holistically through descriptions of words in a natural context. Data were collected through observation, interview, and documentation techniques, with purposive sampling techniques involving principals, teachers, and school staff as the primary informants. The results showed that the exemplary method effectively shapes student character, where students learn moral values by observing teachers as role models. The success of this method is driven by teacher competence and a supportive school environment. The habituation method is also effective through positive habits that are applied regularly, with teachers as facilitators who use positive and negative reinforcement to instill moral values. To improve the effectiveness of both methods, it is recommended that teachers provide more varied examples, utilize interactive learning media, and optimize rewards.